Cloning, Expression, and Functional Characterization of In-House Prepared Human Leukemia Inhibitory Factor - Rassouli, Hassan (Royan Institute, 2013)
OBJECTIVE: Leukemia inhibitory factor (LIF) plays important roles in cellular proliferation, growth promotion and differentiation of various types of target cells. In addition, LIF influences bone metabolism, cachexia, neural development, embryogenesis and inflammation. Human LIF (hLIF) is an essential growth factor for the maintenance of mouse embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) in a pluripotent, undifferentiated state. MATERIALS AND METHODS: In this experimental study, we cloned hLIF into the pENTR-D/ TOPO entry vector by a TOPO reaction. Next, hLIF was subcloned into the pDEST17 destination vector by the LR reaction, which resulted in the production of a construct that was transferred into E. coli strain Rosetta-gami™ 2(DE3) pLacI competent cells to produce the His6-hLIF fusion protein. RESULTS: This straightforward method produced a biologically active recombinant hLIF protein in E. coli that has long-term storage ability. This procedure has provided rapid, cost effective purification of a soluble hLIF protein that is biologically active and functional as measured in mouse ESCs and iPSCs in vitro. CONCLUSION: Our results showed no significant differences in function between laboratory produced and commercialized hLIF